2012
DOI: 10.3126/kumj.v9i4.6353
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Precocious Puberty in a Setting with Limited Resources

Abstract: Precocious puberty is a rare condition characterized by the development of secondary sexual characteristics before the median age for the sex. It is either gonadotropin dependent also called as central or gonadotropin independent also known as peripheral type. Hypothalamamic Hamartoma is a common cause of the central or precocious puberty due to organic brain lesion. Here we present a two year male who presented us with precocious puberty due to a hypothalamic Hamartoma.DOI: http://dx.doi.org/10.3126/kumj.v9i4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 12 publications
0
15
2
Order By: Relevance
“…Most of our cases also involved flame burns to the upper extremity, and the majority of our patients received no formal treatment at the time of injury, presenting months to years later with cosmetic or functional problems due to secondary contractures. Burn contracture was the most common reason for a lower extremity amputation (30%) at our hospital between 1997 and 2004 [36]. The percentage of our surgical cases for burn contractures has not changed substantially compared with a review from 1985 to 1987 [37].…”
Section: Discussionmentioning
confidence: 99%
“…Most of our cases also involved flame burns to the upper extremity, and the majority of our patients received no formal treatment at the time of injury, presenting months to years later with cosmetic or functional problems due to secondary contractures. Burn contracture was the most common reason for a lower extremity amputation (30%) at our hospital between 1997 and 2004 [36]. The percentage of our surgical cases for burn contractures has not changed substantially compared with a review from 1985 to 1987 [37].…”
Section: Discussionmentioning
confidence: 99%
“…Medical treatment is the first choice suggested in GnRH dependent precocious puberty (hypothalamic cause). 18,19 Manoj et al in his retropspective study on 42 cases of Adreno cortical adenoma and adreno cortical carcinoma found Weiss scoring system to be useful in distinguishing the tumors but this was possible only after histopathology. 14 20,22 In Immunohistochemistry staining Chromogranin A, Synaptophysin, S100, Inhibin Alfa was negative which is typical for Pheochromocytoma.…”
Section: Discussionmentioning
confidence: 99%
“…Amputation is a last resort surgical procedure that involved the removal of an external part of the body, such as a limb or part of it as a treatment plan, about 285million people globally are living with limb amputation. Although, loss of a limb create additional health burden and affects the quality of life of the amputee, amputation, however, is deployed to save the patient's life (Paudel et al, 2005 andUdosen et al, 2009). Prosthesis is a device designed to substitute the function or the appearance of a missing limb or body part (Sixtus et al, 2022), to restore mobility and degree of normal functions to amputees (Arvela et al 2010 andBierbaum et al 2002).…”
Section: Introductionmentioning
confidence: 99%